2020
DOI: 10.1073/pnas.2016864117
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine MIF controls daily rhythms of symbiont nutrition in an animal–bacterial association

Abstract: The recent recognition that many symbioses exhibit daily rhythms has encouraged research into the partner dialogue that drives these biological oscillations. Here we characterized the pivotal role of the versatile cytokine macrophage migration inhibitory factor (MIF) in regulating a metabolic rhythm in the model light-organ symbiosis between Euprymna scolopes and Vibrio fischeri. As the juvenile host matures, it develops complex daily rhythms characterized by profound changes in the association, from gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 110 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Haemocytes from the host circulatory system migrate into the light organ where a certain number of these cells lyse, releasing chitin stores that the symbionts metabolize by fermentation 33 . A recent study demonstrated that movement of the haemocytes into the crypts is regulated by a cytokine, macrophage migration inhibitory factor (MIF) 70 . This immune protein is abundant in the symbiotic tissues during the day, perhaps to deter migration of the haemocytes into those regions, and is in low abundance at night, enabling haemocytes to traffic into the crypts to release their chitin stores.…”
Section: Maturation Of the Rhythmsmentioning
confidence: 99%
“…Haemocytes from the host circulatory system migrate into the light organ where a certain number of these cells lyse, releasing chitin stores that the symbionts metabolize by fermentation 33 . A recent study demonstrated that movement of the haemocytes into the crypts is regulated by a cytokine, macrophage migration inhibitory factor (MIF) 70 . This immune protein is abundant in the symbiotic tissues during the day, perhaps to deter migration of the haemocytes into those regions, and is in low abundance at night, enabling haemocytes to traffic into the crypts to release their chitin stores.…”
Section: Maturation Of the Rhythmsmentioning
confidence: 99%
“…The exception is the bobtail squid, of course. Here, the host mechanisms that contribute decisively to the circadian regulation of the abundance of the symbiont Vibrio fischeri were elucidated 19 , 70 , 75 . Despite these efforts, we are currently just beginning to understand this complex interplay and especially the underlying molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%